Simulated changes in atmospheric dust in response to a Heinrich stadial. (15th January 2014) - Murphy, Lisa N.; Clement, Amy C.; Albani, Samuel; Mahowald, Natalie M.; Swart, Peter; Arienzo, Monica M.
Abstract [1] Heinrich stadials (HS), thought to be triggered by increased ice discharge in the high‐latitude North Atlantic at glacial periods, resulted in large freshwater forcing that weakened the Atlantic Meridional Overturning Circulation (AMOC). These events are strongly expressed in paleoclimate records throughout the Atlantic basin and much of the tropics. Compared to the Last Glacial Maximum, recent proxy data suggest HS were much drier and dustier in large parts of the tropics. We use a global climate model coupled to a prognostic dust model to examine the response of dust to changes in climate during HS. Despite some significant changes in regional precipitation patterns in response to the simulated shift in the Intertropical Convergence Zone, we find that changes in winds have a larger effect on dust mobilization and deposition patterns than soil moisture or vegetation changes associated with a weaker AMOC. Although Europe was colder and drier during HS, the annual mean glaciogenic dust emission rate is lower because a southward shift in the Northern Hemisphere jet stream leads to weaker winds and less dust mobilization. The proximity of the westerly wind anomaly associated with the jet stream shift increases gustiness and dust mobilization over northwestern Africa and shifts the African Easterly Jet southward resulting in less African dust transport and deposition over the North Tropical Atlantic. Drier conditions over the Sahel region of North Africa, however, do not lead to increased dust mobilization in our model. When we perturb Sahelian soil characteristics, our results are in better agreement with proxies.